If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x(x+3)+3(x+1)=24
We move all terms to the left:
2x(x+3)+3(x+1)-(24)=0
We multiply parentheses
2x^2+6x+3x+3-24=0
We add all the numbers together, and all the variables
2x^2+9x-21=0
a = 2; b = 9; c = -21;
Δ = b2-4ac
Δ = 92-4·2·(-21)
Δ = 249
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(9)-\sqrt{249}}{2*2}=\frac{-9-\sqrt{249}}{4} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(9)+\sqrt{249}}{2*2}=\frac{-9+\sqrt{249}}{4} $
| 9x+4=12x-3 | | (7n+12)+(6n)+(13n+16)=n | | 3/8(x-6)=15 | | 4x^2+3x-8x=3 | | 8x+7=3x+39 | | x+4+3x=5(3x-2) | | -6x-4x=14 | | 90+(5x+13)+2x=180 | | 15g-10-9g+15=77 | | 3x–7=4x+8 | | 2-4(x+5)=-4x-18 | | C(4)=2x+80 | | -15(r+4)=-15 | | (x+38)+(x+13)+x=180 | | -x/2*3=9 | | 5x+3=3x+28 | | 6(x+6)=7(x–9) | | (1x)+(2x)+(1x)=12 | | 3(w+3)=13 | | 15=11x-3-14x | | 5−3(x+4)=x−7 | | 5(2p-6)=-4(p-4) | | -4x-3=-2x=7 | | 3a−7=7+a | | 7-6y+5y=-11-2y-2y | | (x+7)+127+x=180 | | 1x+1x+2x=12 | | x+7=110 | | 2x+13=x+30 | | 4+2(5x-8)=1 | | 2(s+13)-6=4 | | x+211=360 |